Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1128/mbio.01006-19
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Host Biomarkers of Epstein-Barr Virus Latency IIb and Latency III

Abstract: Deciphering the molecular pathogenesis of virally induced cancers is challenging due, in part, to the heterogeneity of both viral gene expression and host gene expression. Epstein-Barr virus (EBV) is a ubiquitous herpesvirus prevalent in B-cell lymphomas of immune-suppressed individuals. EBV infection of primary human B cells leads to their immortalization into lymphoblastoid cell lines (LCLs), serving as a model of these lymphomas. In previous studies, reports from our laboratory have described a temporal mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
1

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 41 publications
4
21
0
Order By: Relevance
“…The advent of high-throughput, single-cell based methods has revealed a more complex picture of herpesvirus infection, from latent infection (Messinger et al, 2019; Oko et al, 2019; Shnayder et al, 2018), to lytic infection (Drayman et al, 2019; Oko et al, 2019; Wyler et al, 2019), reactivation from latency (Adang et al, 2006; Oko et al, 2019) and viral tropism (Sen et al, 2014). Recently, we identified unanticipated heterogeneity between infected cells during lytic infection, with wide variance in viral gene expression, from cells with robust viral gene expression to cells with little to no detectable expression of either viral non-coding RNAs or mRNAs (Oko et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The advent of high-throughput, single-cell based methods has revealed a more complex picture of herpesvirus infection, from latent infection (Messinger et al, 2019; Oko et al, 2019; Shnayder et al, 2018), to lytic infection (Drayman et al, 2019; Oko et al, 2019; Wyler et al, 2019), reactivation from latency (Adang et al, 2006; Oko et al, 2019) and viral tropism (Sen et al, 2014). Recently, we identified unanticipated heterogeneity between infected cells during lytic infection, with wide variance in viral gene expression, from cells with robust viral gene expression to cells with little to no detectable expression of either viral non-coding RNAs or mRNAs (Oko et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Our lab has found that the early-and late-phases of EBV are transcriptionally distinct (Messinger et al, 2019) and utilize unique strategies to promote apoptosis resistance (Price et al, 2017). Apoptosis is regulated by complex protein-protein interactions between pro-apoptotic and anti-apoptotic members of the BCL2 protein family.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, we recently described a gene expression program having low expression of LMP1 and NFκB targets which was unique to early infection (Latency IIb) relative to an otherwise identical population of LCLs. 30 The wide distribution in LMP1 and NFκB target expression levels within an LCL has been characterized and ascribed to the dynamic sampling of a distribution of immune evasive states, at the fringes of which growth and survival can be compromised. 3133…”
Section: Introductionmentioning
confidence: 99%